ANALISIS PERAN PERAWAT TERHADAP KETEPATAN PENETUAN PRIORITAS I, II DAN III PADA RUANG TRIAGE DI INSTALASI GAWAT DARURAT RUMAH SAKIT DR. SAIFUL ANWAR MALANG - Ardiyani, Vita Maryah (JURNAL NERS LENTERA, 2018)
Introduction: The emergency room is integrated units because all the front line in guarding upon a hospital who are in need an appropriate and effective triage system to select and prioritize perceived patients according to the condition of a patient and source .A mistake the decision making process , more positive light especially in separate patients with two categories of poor of the number triage cause delays at the treatment and inability as well as permanently disabled to be the responsibility of triage nurse who often seeking inquiring for craving to continue to develop their role in taken the right decisions especially in the determination of the emphasis on the emergency priority on the emergency room .The purpose of of the study are to analyze the relation of the role of the triage nurse to the determination of the emphasis on the emergency priority in installationUnit . Method: This research is a cross section analytic ( analytic of cross sectional study ) by applying a technique quota the sampling method of as many as 200 patients during the emergency room. Technique the data using sheets of observation the role of nurses and a observation triage that has been in do test numerator kappa.The results of the chi square and obtained the results of p value 0.000 with significance level of 0.05 Discussion: The accuracy of emergency priority in the triage is also affected experience clinical nurse where the concept of the determination of priority based on the criteria p1, p2 and p3 in general have been controlled by nurses.Conclusion: There are the relationship between the role of a nurse with the determination of emergency priority. Keywords: role of nurses, emegency priority, triage